Potassium-solubilizing bacteria mediated soil potassium dynamics in sweet corn - Kundu, S; Sudhakar, SK; Gade, KR; Laxminarayana, P; Kumar, SV; Goud, GMK; Banoth, SK; Erapuram, P (Plant Science Today, 2026)
Potassium (K) is an indispensable macronutrient for plant growth and development and is immensely important for agriculture. Potassium-solubilising bacteria (KSB) have gained importance due to their dual functionality as plant growth-promoting rhizobacteria (PGPR) and their ability to solubilise unavailable forms of soil potassium. This study assessed the potential of dual-mode application of KSB (seed treatment + soil drenching) on soil potassium fraction dynamics, nutrient uptake and yield of a heavy feeder crop (sweet corn). The experiment was conducted at the College Farm, Professor Jayashankar Telangana Agricultural University (PJTAU), Hyderabad, during the winter season (19 November 2022 to 23 February 2023). Results demonstrated that among different treatments, application of 100 % recommended dose of K (RDK; 50 kg ha-1) ± KSB (Bacillus amyloliquefaciens) (Seed Treatment (ST) at 10 mL kg-1 seed + soil drenching (SD) at 2.5 mL L-1 water at 25 DAS) and 75 % RDK + KSB (ST + SD) resulted in significantly higher available soil K fractions and consequently, higher K uptake and sweet corn yield were observed with these treatments. Higher monetary returns per unit cost were recorded with recommended K fertiliser; however, they were statistically at par with 75 % RDK + KSB (ST + SD). There was a synergistic effect between N and K uptake. However, P uptake was not significantly affected by K management practices. Non-exchangeable K (Non-ExK) content remained unchanged due to treatment imposition. However, all soil K fractions viz., water-soluble K, exchangeable K (ExK) and Non-ExK, showed a numerically declining trend during the crop growth period.